The unmanageable consumer : contemporary consumption and its fragmentation - Gabriel, Yiannis (Sage Publications, 1995)
Consumption and concepts of the consumer sit at the centre of numerous current debates - academic, political and environmental. This highly readable and stimulating book, a tour-de-force in the breadth of its coverage and analysis, shows how different traditions (discourses) have constructed different representations of the consumer. Each of these has its own coherence but rarely addresses alternative positions.